Influence of breast cancer subtype on pathological complete response - Mancinelli, Bruno de Carvalho; Antonini, Marcelo; Silva, Flávia Vasconcelos da; Ferraro, Odair; Lopes, Reginaldo Guedes Coelho (Mastology, 2020)
1. Brasil. Ministério da Saúde. Tipos de câncer: câncer de mama [Internet]. Brasil: Instituto Nacional do Câncer [acessed on July 17, 2017]. Available at: http://www2.inca.gov.br/wps/wcm/ connect/tiposdecancer/site/home/mama/cancer_mama 2. Bardia A, Baselga J. Neoadjuvant therapy as a platform for drug development and approval in breast cancer. Clin Cancer Res. 2013;19(23):6360-70. https://doi.org/10.1158/1078-0432. ccr-13-0916 3. Ueno NT, Buzdar AU, Singletary SE, Ames FC, McNeese MD, Holmes FA, et al. Combined-modality treatment of inflammatory breast carcinoma: Twenty years of experience at M.D. Anderson Cancer Center. Cancer Chemother Pharmacol. 1997;40(4):321-9. https://doi.org/10.1007/s002800050664 4. Pachnick JPA, Czeczko NG, Tuon F, Cavalcanti TS, Malafaia AB, Tuleski AM. Avaliação imunoistoquímica dos receptores de estrogênio e progesterona no câncer de mama, pré e pósquimioterapia neoadjuvante. Rev Col Bras Cir. 2012;39(2):86- 91. https://doi.org/10.1590/S0100-69912012000200002 5. Schwartz GF, Hortobagyi GN. Proceedings of the consensus conference on neoadjuvant chemotherapy in carcinoma of the breast, April 26-28, 2003, Philadelphia, Pennsylvania. Cancer. 2004;100(12):2512-32. https://doi.org/10.1002/cncr.20298 6. Mamtani A, Barrio AV, King TA, Van Zee KJ, Plitas G, Pilewskie M, et al. How Often Does Neoadjuvant Chemotherapy Avoid Axillary Dissection in Patients With Histologically Confirmed Nodal Metastases? Results of a Prospective Study. Ann Surg Oncol. 2016;23(11):3467-74. https://dx.doi. org/10.1245%2Fs10434-016-5246-8 REFERENCES 7. Spring L, Greenup R, Niemierko A, Schapira L, Haddad S, Jimenez R, et al. Pathologic complete response after neoadjuvant chemotherapy and long-term outcomes among young women with breast cancer. J Natl Compr Cancer Netw. 2017;15(10):1216-23. https://doi.org/10.6004/jnccn.2017.0158 8. Rastogi P, Anderson SJ, Bear HD, Geyer CE, Kahlenberg MS, Robidoux A, et al. Preoperative chemotherapy: Updates of national surgical adjuvant breast and bowel project protocols B-18 and B-27. J Clin Oncol. 2008;26(5):778-85. https://doi. org/10.1200/jco.2007.15.0235 9. Gralow JR, Burstein HJ, Wood W, Hortobagyi GN, Gianni L, Von Minckwitz G, et al. Preoperative therapy in invasive breast cancer: Pathologic assessment and systemic therapy issues in operable disease. J Clin Oncol. 2008;26(5):814-9. https://doi. org/10.1200/jco.2007.15.3510 10. Cortazar P, Zhang L, Untch M, Mehta K, Costantino JP, Wolmark N, et al. Pathological complete response and long-term clinical benefit in breast cancer: The CTNeoBC pooled analysis. Lancet. 2014;384(9938):164-72. https://doi. org/10.1016/s0140-6736(13)62422-8 11. Carey LA, Dees EC, Sawyer L, Gatti L, Moore DT, Collichio F, et al. The triple negative paradox: Primary tumor chemosensitivity of breast cancer subtypes. Clin Cancer Res. 2007;13(8):2329-34. https://doi.org/10.1158/1078-0432.ccr-06-1109 12. Precht LM, Lowe KA, Atwood M, Beatty JD. Neoadjuvant chemotherapy of breast cancer: Tumor markers as predictors of pathologic response, recurrence, and survival. Breast J. 2010;16(4):362-8. https://doi.org/10.1111/j.1524-4741.2010.00935.x indication of conservative surgery in patients who, initially, are not candidates for the procedure. Axillary emptying was necessary in 89.3% of cases, similar results reported by Van Vaisberg et al.17, in which 85% of patients were submitted to axillary emptying. Such data can be explained by the higher percentage of advanced stages and, in addition, during the sample collection period, axillary emptying was the choice in the case of clinically compromised armpits (N1+). Mamtani et al.6 and Donker et al.18 found that, with the increase in indications for sentinel lymph node biopsy in cases of clinical response in the axilla, axillary emptying rates were reduced by 60%. It is known that the NACT response is greater in tumors with negative ER, TN, positive HER2. We could observe that the pure HER2 (37.9%) and luminal B HER (41.2%) subtypes presented the highest pCR rates. Data reported by Boughey et al.19 and Silva et al.20 confirm similar values (45.4%). In our study, no dual anti-HER2 therapy was performed in a neoadjuvant environment. As per publication by Nitz et al.21, it is known that pCR rates for tumors with HER2 overexpression can reach up to 70%. In TNBC, the rate of 24.2% of pCR was lower than that reported by Spring et al.7 in their meta-analysis; however, it should be noted that the lack of standardization of NACT schemes observed in this sample may have influenced the pCR rate verified in this study, bringing limitations to the comparison with current references. Therefore, it should be noted that the limitations of this study stem from the lack of standardized schemes for NACT, which makes it difficult to compare pCR rates in different breast cancer subtypes. In addition, some of the drugs used in major world centers were not available at the hospital chosen for assessment, making the pCR rate of some subtypes (for example tumors with HER2 overexpression) lower than current data. Further studies are suggested, with the standardization of chemotherapy schemes and the use of new drugs already approved. CONCLUSION Although the pCR rate varies according to breast cancer subtype, pure HER2 and luminal B HER2 subtypes were the ones with the highest rates. 5 Influence of breast cancer subtype on pathological complete response Mastology 2020;30:e20200007 © 2020 Brazilian Society of Mastology This is an open access article distributed under the terms of the Creative Commons license. 13. Monteiro H de AV, Goulart-Citrangulo SMT, Leite MS, Giacomin LC, Vianna-Jorge R. Influência de Variáveis Clinicopatológicas sobre a Eficácia da Quimioterapia Neoadjuvante do Câncer de Mama. Rev Bras Cancerol. 2013;59(3):369-77. 14. Santos TP, Paes MA, Ferreira ACS de M, Campos T. Avaliação epidemiológica das pacientes com câncer de mama tratadas com trastuzumabe no Hospital de Base de Brasília. Rev Bras Oncol Clínica. 2014;10(36):55-9. 15. Lopes LAF, Linhares, JJ, Ferraro O, Guedes R, Lopes C, Baracat FF. Valor prognóstico do grau histológico (GH), grau nuclear (GN) e índice mitótico (IM) para pacientes com carcinoma da mama estádios II e III com linfonodos axilares comprometidos. Rev Bras Cancerol. 2006;52(3):245-51. 16. Aquino RGF de, Pinheiro LGP, Cavalcante DIM, Vasques PHD, Oliveira AL de S, Silva CAB da. Carcinoma ductal invasor: comparação dos graus histológicos entre tumor primário e metástase axilar. Rev Bras Mastol. 2016;26(2):45-9. 17. Van Vaisberg V, Vilas Boas MDS, Stephan BDO, Matutino ARB, Lima JMDS, Mano MS. Câncer de mama: efeito prognóstico da resposta patológica completa após quimioterapia neoadjuvante. Rev Med. 2015;94(Supl.):31. https://doi. org/10.11606/issn.1679-9836.v94isupl.p31-31 18. Donker M, van Tienhoven G, Straver ME, Meijnen P, van de Velde CJH, Mansel RE, et al. Radiotherapy or surgery of the axilla after a positive sentinel node in breast cancer (EORTC 10981- 22023 AMAROS): A randomised, multicentre, open-label, phase 3 non-inferiority trial. Lancet Oncol. 2014;15(12):1303- 10. http://dx.doi.org/10.1016/S1470-2045(14)70460-7 19. BougheyJC, SumanVJ, MittendorfEA, AhrendtGM, WilkeLG, Taback B, et al. Sentinel lymph node surgery after neoadjuvant chemotherapy in patients with node-positive breast cancer: The ACOSOG Z1071 (alliance) clinical trial. J Am Med Assoc. 2013;310(14):1455-61. https:// dx.doi.org/10.1001%2Fjama.2013.278932 20. Silva EHL de S, Paloschi JRA, Caldeira JR de F, Joioso A. Estudo comparativo de resposta à quimioterapia neoadjuvante em dose total, entre câncer de mama e metástase axilar, conforme resultados de imunoistoquímica, no Serviço de Mastologia do Hospital Amaral Carvalho em Jaú, SP. Rev Bras Mastol. 2015;25(2):46-50. https://dx.doi.org/10.5327/Z201500020003RBM 21. Nitz U, Gluz O, Christgen M, Grischke EM, Augustin D, Kümmel S, et al. Final analysis of WSG-ADAPT HER2+/HR- trial: Efficacy, safety, and predictive markers for 12-weeks of neoadjuvant dual blockade with trastuzumab + pertuzumab ± weekly paclitaxel in HER2+/HR- early breast cancer (EBC). J Clin Oncol. 2016;34(15 Supl.):518. https://dx.doi.org/10.1200/JCO.2016.34.15_suppl.518